The 88-Inch Cyclotron: A one-stop facility for electronics radiation and detector testing. (October 2018) - Kireeff Covo, M.; Albright, R.A.; Ninemire, B.F.; Johnson, M.B.; Hodgkinson, A.; Loew, T.; Benitez, J.Y.; Todd, D.S.; Xie, D.Z.; Perry, T.; Phair, L.; Bernstein, L.A.; et al.
Abstract: In outer space down to the altitudes routinely flown by larger aircrafts, radiation can pose serious issues for microelectronics circuits. The 88-Inch Cyclotron at Lawrence Berkeley National Laboratory is a sector-focused cyclotron and home of the Berkeley Accelerator Space Effects Facility, where the effects of energetic particles on sensitive microelectronics are studied with the goal of designing electronic systems for the space community. This paper describes the flexibility of the facility and its capabilities for testing the bombardment of electronics by heavy ions, light ions, and neutrons. Experimental capabilities for the generation of neutron beams from deuteron breakups and radiation testing of carbon nanotube field effect transistor will be discussed.